Towards Thermally Reversible Networks Based on Furan-Functionalization of Jatropha Oil - Yuliati, Frita; Deuss, Peter J.; Heeres, Hero J.; Picchioni, Francesco (Molecules (Basel, Switzerland), 2020)
A novel biobased monomer for the preparation of thermally reversible networks based on the Diels-Alder reaction was synthesized from jatropha oil. The oil was epoxidized and subsequently reacted with furfurylamine to attach furan groups via an epoxide ring opening reaction. However, furfurylamine also reacted with the ester groups of the triglycerides via aminolysis, thus resulting in short-chain molecules that ultimately yielded brittle thermally reversible polymers upon cross-linking via a Diels-Alder reaction. A full-factorial experimental design was used in finding the optimum conditions to minimize ester aminolysis and to maximize the epoxide ring opening reaction as well as the number of furans attached to the modified oil. The optimum conditions were determined experimentally and were found to be 80 °C, 24 h, 1:1 molar ratio, with 50 mol % of LiBr with respect to the modified oil, resulting in 35% of ester conversion, 99% of epoxide conversion, and an average of 1.32 furans/triglyceride. Ultimately, further optimization by a statistical approach led to an average of 2.19 furans per triglyceride, which eventually yielded a flexible network upon cross-linking via a Diels-Alder reaction instead of the brittle one obtained when the furan-functionalization reaction was not optimized.